Dry sliding friction behaviour of ALCRN and tin coating - Mohd Azlan Ismail; Willey Liew; Sebastian Dayou (Universiti Malaysia Sabah, 2012)
This thesis examine the friction and wear behaviour of AICrN and TiN PVD coatings using the ball-on-disc and reciprocating tests. Comparative study on the coatings in air and vacuum environment was aimed to provide important insight on the effect of oxidation on the friction behaviour of the coatings. Other important factors such as load, sliding velocity and temperature effects on the coatings were also investigated. In the ball-on-disc tests carried out in vacuum, (i) TiN gave lower COF than AICrN, showing that the surface of TiN was more lubricous, and (ii) the COF of both coatings were lower than that produced in air. In ambient air, AICrN gave lower COF than TiN with high wear debris retention on the sliding interface due to the effect of oxidation. In the reciprocating tests, increasing the temperature from room temperature to 150°C resulted in a reduction in the COF. Higher nominal load resulted in lower COF while higher speed resulted in higher COF